Analisis Faktor-Faktor Yang Mempengaruhi Minat Individu Terhadap Penggunaan Sistem Informasi Akuntansi Berbasis E-Commerce (Studi Kasus pada Mahasiswa Akuntansi Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta) - Widyanitami, Yulita; , Dr. Erma Setiawati, MM.,CA (2017)
This study purposes to examine the factors that influence intention of behaviouron the use e-commerce system. Samples of this research were students of Accounting Majors at Economic and Business Faculty of Muhammadiyah University in Surakarta who ever useelectronic commerce. A total of 95 data were processed using software SPSS version 16.0. The analysis results of this research indicate that the perceived privacy, perceived risk, perceived usefulness, and perceived ease of use affect the intention to use e-commerce. Even though that perceived security and perceived trust did not influence the intention to use e-commerce. This means that the intention in using e-commerce system is influenced by perceived privacy, perceived risk, perceived usefulness, and perceived ease of use. Implications of this research are expected to assist online bussiness sector to take notice factors that affect intention to use e-commerce system in implementing and developing e-commerce system.